Exploring the role of dynamic capabilities in digital circular business model innovation: Results from a grounded systematic inductive analysis of 7 case studies. (15th May 2023) - van Eechoud, Thomas; Ganzaroli, Andrea
Abstract: There is already extensive literature that focuses on the leading role of digital technologies in fostering circular business model innovation. However, little attention has been paid so far to the dynamic capabilities involved in the digitally enabled transition from linear to circular. We contribute to reducing this gap by proposing an empirically grounded theoretical framework on the role of dynamic capabilities in digital circular business model innovation. Our contribution is grounded on the systemic inductive analysis based on the Gioia methodology of 7 in-depth semi-structured interviews with managers in charge of digital circular business model innovation. Companies were selected for their SASB materiality index and levels of technological intensity. Our findings highlight the role of dynamic capability in sensing and seizing digital circular business model innovation and, in particular, supply chain collaboration, lean methodologies, and project management. Highlights: Dynamic capabilities are critical in enabling digital circular business model innovation. Digital circular business model innovation requires integrating digital and environmental competencies. Supply chain collaboration is fundamental for achieving success in digital business model innovation. Lean management is critical to and maximizing engagement in digital circular business model innovation.